2017
DOI: 10.5005/jp-journals-10018-1233
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in the Treatment of Nonalcoholic Fatty Liver Disease: A Meta-analysis

Abstract: Aim:Despite extensive ongoing research, there is scarcity of widely accepted therapeutic options for the treatment of nonalcoholic fatty liver disease (NAFLD). Probiotics are a promising treatment option for treating NAFLD; however, their effectiveness needs to be established. Since any single randomized controlled trial (RCT) cannot establish the role of probiotics in the treatment of NAFLD, this study aims at meta-analysis of different RCTs.Materials and methods:Extensive search was done by two independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…In our study we observed a significantly lower ALT serum concentration in the group receiving a higher dose of probiotic compared to the control group. The results of our study are in line with recent meta-analysis of 7 human double-blinded RCTs and comparative studies performed by Lavekar et al (2017), who reported a significant reduction in blood ALT activity after probiotic supplementation in the period ranging from 2 to 7 months. Moreover, the meta-analysis of Lavekar et al (2017) has confirmed the decrease in BMI and blood AST concentration after a probiotic is supplied.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study we observed a significantly lower ALT serum concentration in the group receiving a higher dose of probiotic compared to the control group. The results of our study are in line with recent meta-analysis of 7 human double-blinded RCTs and comparative studies performed by Lavekar et al (2017), who reported a significant reduction in blood ALT activity after probiotic supplementation in the period ranging from 2 to 7 months. Moreover, the meta-analysis of Lavekar et al (2017) has confirmed the decrease in BMI and blood AST concentration after a probiotic is supplied.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study are in line with recent meta-analysis of 7 human double-blinded RCTs and comparative studies performed by Lavekar et al (2017), who reported a significant reduction in blood ALT activity after probiotic supplementation in the period ranging from 2 to 7 months. Moreover, the meta-analysis of Lavekar et al (2017) has confirmed the decrease in BMI and blood AST concentration after a probiotic is supplied. Supplementation with Lactobacillus bulgaricus and Streptococcus thermophilus have been shown to reduce not only ALT and AST, but also the gamma-glutamyltransferase (GGT) serum level in patients with NAFLD (Aller et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors also noted that BMI, glucose, and low‐density lipoprotein did not improve after probiotic treatment . Recently, several meta‐analyses have evaluated the effects of probiotics on liver histology . The authors did report the favorite effects of probiotic in NASH.…”
Section: Anti‐oxidants and Cytoprotective Therapiesmentioning
confidence: 99%
“…At present, however, there is no uniformity in the outcomes assessed. Moreover, it remains to be elucidated whether the type of microbial therapy, the dose used of treatment, and the duration of therapy affect outcomes or not …”
Section: Anti‐oxidants and Cytoprotective Therapiesmentioning
confidence: 99%